Fiscal policy under imperfect competition with flexible prices: An overview and survey - Luís F. Costa; Huw David Dixon (Economics: The Open-Access, Open-Assessment E-Journal, 2011)
This paper surveys the link between imperfect competition and the effects of fiscal policy on output, employment and welfare. We examine static and dynamic models, with and without entry under a variety of assumptions using a common analytical framework. We find that in general there is a robust relationship between the fiscal multiplier and welfare, the tantalizing possibility of Pareto improving fiscal policy is much more elusive. In general, the mechanisms are supply side, and so welfare improving policy, whilst possible, is not a general result.
Keywords: E62; 330; Fiscal policy; imperfect competition; Finanzpolitik; Unvollkommener Wettbewerb; Wirkungsanalyse; Konjunktur; Beschäftigungseffekt; Wohlfahrtseffekt; Theorie